Peran Inklusi Keuangan dalam Memediasi Pengaruh Mental Accounting dan Financial Technology terhadap Kinerja UMKM di Kabupaten Grobogan - Astohar Astohar; Emi Wardati; Tri Sumiyanti; Shelly Geovanni (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
MSMEs are a supporting sector of the country's economy and are able to survive in various conditions that occur in Indonesia. MSMEs are able to contribute to increasing national income and also help in absorbing labor as a result of increasing the performance of these MSMEs. Many factors that influence performance between mental accounting and financial technology are mediated by financial inclusion. The results of a preliminary survey on MSMEs in Grobogan Regency show that the average performance of MSMEs is still fluctuating. The object of this research was carried out on MSMEs in Grobogan Regency with a final sample size of 158 using the cluster random sampling method. The analysis tool uses a regression equation test with a mediation test using the Sobel test. The results of the descriptive analysis show that the variables mental accounting, financial technology, MSME financial inclusion and MSME performance in Grobogan Regency are in the sufficient category (2.33 to 3.65), with financial technology with the highest average. The mental accounting and financial technology variables are proven to have a positive and significant effect on the financial inclusion of MSMEs in Grobogan Regency. Mental accounting, financial technology and MSME financial inclusion are proven to influence the performance of MSMEs in Grobogan Regency. MSME financial inclusion is proven to mediate the influence of mental accounting and financial technology on MSME performance in Grobogan Regency.